Chlorella vulgaris Extract as a Serum Replacement That Enhances Mammalian Cell Growth and Protein Expression - Ng, Jian Yao; Chua, Mei Ling; Zhang, Chi; Hong, Shiqi; Kumar, Yogesh; Gokhale, Rajeev; Ee, Pui Lai Rachel (Frontiers in Bioengineering and Biotechnology, 2020)
The global cell culture market is experiencing significant growth due to the rapid advancement in antibody-based and cell-based therapies. Both rely on the capacity of different living factories, namely prokaryotic and eukaryotic cells, plants or animals for reliable and mass production. The ability to improve production yield is of important concern. Among many strategies pursued, optimizing the complex nutritional requirements for cell growth and protein production has been frequently performed via culture media component titration and serum replacement. The addition of specific ingredients into culture media to modulate host cells’ metabolism has also recently been explored. In this study, we examined the use of extracted bioactive components of the microalgae Chlorella vulgaris, termed chlorella growth factor (CGF), as a cell culture additive for serum replacement and protein expression induction. We first established a chemical fingerprint of CGF using ultraviolet-visible spectroscopy and liquid chromatography-mass spectrometry and evaluated its ability to enhance cell proliferation in mammalian host cells. CGF successfully promoted the growth of Chinese hamster ovary (CHO) and mesenchymal stem cells (MSC), in both 2D and 3D cell cultures under reduced serum conditions for up to 21 days. In addition, CGF preserved cell functions as evident by an increase in protein expression in CHO cells and the maintenance of stem cell phenotype in MSC. Taken together, our results suggest that CGF is a viable culture media additive and growth matrix component, with wide ranging applications in biotechnology and tissue engineering.